The effect of age and gender on anti‐saccade performance: Results from a large cohort of healthy aging individuals. (5th July 2020) - Mack, David J.; Heinzel, Sebastian; Pilotto, Andrea; Stetz, Lena; Lachenmaier, Sandra; Gugolz, Leonie; Srulijes, Karin; Eschweiler, Gerhard W.; Sünkel, Ulrike; Berg, Daniela; Ilg, Uwe J.
Abstract: By 2050, the global population of people aged 65 years or older will triple. While this is accompanied with an increasing burden of age‐associated diseases, it also emphasizes the need to understand the effects of healthy aging on cognitive processes. One such effect is a general slowing of processing speed, which is well documented in many domains. The execution of anti‐saccades depends on a well‐established brain‐wide network ranging from various cortical areas and basal ganglia through the superior colliculus down to the brainstem saccade generators. To clarify the consequences of healthy aging as well as gender on the execution of reflexive and voluntary saccades, we measured a large sample of healthy, non‐demented individuals ( n  = 731, aged 51–84 years) in the anti‐saccade task. Age affected various aspects of saccade performance: The number of valid trials decreased with age. Error rate, saccadic reaction times (SRTs), and variability in saccade accuracy increased with age, whereas anti‐saccade costs, accuracy, and peak velocity of anti‐saccades and direction errors were not affected by age. Gender affected SRTs independent of age and saccade type with male participants having overall shorter SRTs. Our rigid and solid statistical testing using linear mixed‐effect models provide evidence for a uniform slowing of processing speed independent of the actually performed eye movement. Our data do not support the assumption of a specific deterioration of frontal lobe functions with aging. Abstract : Mack and colleagues analyzed close to 60, 000 saccades performed by 731 participants to examine the effect of age and gender on the parameters of anti‐saccades and direction errors. Their main findings are that saccadic reaction times and error‐rates increase with age. Precision and dynamic parameters of saccades remain constant in the examined age segment. Male participants have shorter reaction times as females in general.